Effects of swimming frequency on body weight and serum lipid profile in small-breed dogs during a four-month period - Nganvongpanit K. (2017)
Lack of activities for dogs, that is, decreased body motion and lack of opportunities to exercise, can cause dogs to become overweight. Swimming is one of the best physical exercises for a dog that has been approved by a veterinary doctor, and it provides a form of supported exercise. Almost all the muscles are required for the movement that involves improving strength, working the cardiovascular and respiratory system, and increasing the metabolic rate withoutimpact on joints. One interesting aspect of swimming is its ability for weight and serum lipid control. The effect of frequency-controlled swimming activity on a dog's weight and its effect on the serum lipid profile level have been well examined and recorded in this study. The dogs were randomly categorized into four groups that swam every day, four times a week, two times a week, and once a week, respectively. The dogs exercised twice a day for 20 minutes each time. The swimming program was continued for a period of four months. Swimming every day significantly reduced the dogs' weight and cholesterol level after one month, while swimming four days per week significantly reduced weight and cholesterol level after four months. After just one month of swimming four days per week, serum triglyceride level was found to be significantly reduced compared with the other groups. HDL level decreased steadily until the third month in the group that swam every day. However, in all the groups, no significant changes were found in the levels of LDL and VLDL in dog serum after 4 months of swimming. In conclusion, higher frequency of swimming per week yields better results than lower frequency for weight and serum lipid control.